2006
DOI: 10.1111/j.1445-6664.2006.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual phytotoxic activity of pethoxamid in soil and its concentration in soil water under different soil moisture conditions

Abstract: The relationship between the residual phytotoxic activity of pethoxamid (2-chloro-N-[2-ethoxyethyl]-N-[2-methyl-1-phenyl-1-propenyl] acetamide) on rice (Oryza sativa cv. Kiyohatamochi) seedlings and its behavior in soil was investigated under different moisture conditions. The phytotoxic activity of pethoxamid on the shoot growth of rice seedlings in soil was higher in 80% soil moisture content than in 70% and 60% soil moisture contents. The phytotoxic activity in soil in 70% and 80% soil moisture conditions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
(23 reference statements)
1
9
1
Order By: Relevance
“…The highest total differences in pethoxamid amount (P = 0.0007) were recorded between irrigated and non-irrigated treatments. These results are in contrast to the results of Dhareesank et al (2006). They found a similar pethoxamid concentration decrease in both the liquid and solid soil phases under different soil moisture conditions.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The highest total differences in pethoxamid amount (P = 0.0007) were recorded between irrigated and non-irrigated treatments. These results are in contrast to the results of Dhareesank et al (2006). They found a similar pethoxamid concentration decrease in both the liquid and solid soil phases under different soil moisture conditions.…”
Section: Resultscontrasting
confidence: 99%
“…The activity of pethoxamid in the soil depends on the decrease of its concentration in soil water with time, except under conditions of low soil moisture insufficient for seedling growth (Dhareesank et al 2006).…”
mentioning
confidence: 99%
“…High weed densities led to yield losses of sunflower, especially on non-irrigated plots. According to Dhareesank et al (2006), the activity of pethoxamid depends on changes in its concentration in soil over time, except when low soil moisture does not allow weed emergence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well known that herbicide activity is affected by soil conditions, including soil property and water conditions. Recently, it was reported that the residual phytotoxic activity of pethoxamid (2‐chloro‐ N‐ [2‐ethoxyethyl]‐ N‐ [2‐methyl‐1‐phenyl‐1‐propenyl] acetamide) in upland soil depended on its decreasing concentration in the soil water with time (Dhareesank et al . 2006).…”
Section: Introductionmentioning
confidence: 99%